Pengaruh Kualitas Pelayanan, Harga, Dan Promosi Terhadap Kepuasan Pelanggan My Beauty Studio - Eldaprilia, Shafina; Meirisa, Faradila (Universitas Multi Data Palembang, 2024)
My Beauty Studio, one of the businesses engaged in beauty care services, this salon provides Creambath, Nail Art, Eyelash, and other hair care services This study aims to determine the effect of Service Quality, Price, and promotion on My Beauty Studio Customer Satisfaction. The sample in this study amounted to 335 using the purposive sampling method with the criteria of having used the services of My Beauty Studio at least 2 times. This study used spss version 26 data. The results of the study for the partial test with the calculated t value for the Service Quality variable were 6.134 with a significant value of 0.000, the calculated t value of the price variable was 7.420 with a significant of 0.000, the calculated t value of the Promotion variable was 9.773 with a significance of 0.000, For the simultaneous test the calculated f value was 317,293 with a significant of 0.000<0.05. The adjusted R square value is .740 or 74%. The conclusion of this study is that Service Quality, Price, and Promotion have a positive and significant effect on Customer Satisfaction at My Beauty Studio.